Evaluation of reclaimed asphalt pavement materials from ultra-thin bonded bituminous surface - Musty, Haritha Yadav (Kansas State University, 2012)
The ultra-thin bonded bituminous surface (UBBS), popularly known as Novachip, is a thin hot-mix asphalt layer with high-quality, gap-graded aggregates bonded to the existing surface with a polymer-modified emulsion membrane. This thin surfacing improves ride quality, reduces road-tire noise, minimizes back spray, and increases visibility under wet conditions. The Kansas Department of Transportation (KDOT) has been using UBBS since 2002. Performance of this thin surface treatment strategy has been good in Kansas and elsewhere. However, some of these projects are now being rehabilitated. The objective of this study is to evaluate whether reclaimed asphalt pavement (RAP) materials from existing UBBS layers can be used in chip seal and Superpave mixtures. UBBS millings were studied with two different polymer-modified emulsions to assess their performance as precoated aggregates in chip seal. The ASTM D7000-04 sweep test was used to assess chip retention of UBBS millings. Three different mix designs were developed for both 12.5-mm and 9.5-mm nominal maximum aggregate size (NMAS)Superpave mixtures using a PG 70-22 asphalt binder and three different percentages (0%, 10%, and 20%) of reclaimed UBBS materials. The designed Superpave mixes were then tested for performance in terms of rutting and stripping using the Hamburg wheel tracking device (HWTD)and moisture sensitivity by modified Lottman tests. Sweep test results showed that UBBS millings did not improve chip retention. Superpave mix design data indicated volumetric properties of Superpave mixes with UBBS millings met all requirements specified by KDOT. HWTD and modified Lottman test results indicated all designed mixes performed better with the addition of UBBS millings as RAP materials. Field performance of UBBS projects was also evaluated. It was found that pavements treated with UBBS showed high variability in service life with majority serving six years. Before and after (BAA) studies showed that UBBS reduces pavement roughness, transverse and fatigue cracking one year after the treatment. However, no consistent improvement in rutting condition was found.
Keywords: Ultra-Thin Bonded Bituminous Surface; Chip Seal; Reclaimed Asphalt Pavement; Rutting; Moisture Susceptibilty; Hamburg Wheel Tracking Device; Civil Engineering (0543)